Modelling of Power Converters Using Z-Transform - Dobrucky, Branislav; Pokorny, Michal; Benova, Mariana; Rzig Abdalmula, Mahmud Ali (Communications - Scientific letters of the University of Zilina, 2013)
The paper introduces a novel method of analysis and modelling of power electronic converters. Z-transform, numerical series (sequences) are used for both steady and transient states investigation of converters. The new impulse switching functions are created which are used as exciting functions of one- and multidimensional state-space models. Theoretical waveforms are compared with simulation results.